Inpatient Management of Diabetic Foot Infections: A Review of the Guidelines for Hospitalists. Issue 12 (20th September 2017) - Thurber, Emilia G.; Kisuule, Flora; Humbyrd, Casey; Townsend, Jennifer
Abstract : Diabetic foot infections (DFIs) are common and represent the leading cause for hospitalization among diabetic complications. Without proper management, DFIs may lead to amputation, which is associated with a decreased quality of life and increased mortality. However, there is currently significant variation in the management of DFIs, and many providers fail to perform critical prevention and assessment measures. In this review, we will provide an overview of the diagnosis, management, and discharge planning of hospitalized patients with DFIs to guide hospitalists in the optimal inpatient care of patients with this condition.